Protracted primary cytomegalovirus infection presenting as ileoanal pouchitis in a non-immunosuppressed patient: a case report - Rupp, Christian; Herpel, Esther; Schnitzler, Paul; Zawierucha, Anna; Zwickel, Philipp; Klute, Lukas; Kadmon, Martina; Stremmel, Wolfgang; Gauss, Annika (Journal of medical case reports, 2014)
Pouchitis often occurs after proctocolectomy and ileal pouch-anal anastomosis for ulcerative colitis. It is usually deemed idiopathic and commonly responds to antibacterial therapy. To date, only a few cases of cytomegalovirus pouchitis have been documented, and only a single report describes pouchitis in a case of assumed primary cytomegalovirus infection.